Length-Weight and Length-Length Relationships of Etrumeus golanii DiBattista, Randall & Bowen, 2012 (Clupeiformes: Dussumieriidae) in Antalya Bay (Mediterranean Sea of Türkiye) - Dilek Türker; Raziye Tanrıverdi; Kadriye Zengin (Aquatic Sciences and Engineering)
Some population biology characteristics of Etrumeus golanii DiBattista, Randall & Bowen, 2012 were estimated for 438 individuals captured using gillnets in Antalya Bay (Mediterranean Sea of Turkey) between November 1997 and May 1998. Fish size in TL (total length) ranged from 8 cm to 26.4 cm and the length-weight relationships (LWRs) were calculated for males, females and all individuals as W=0.0042L3.2309, W=0.0086L2.999 and W=0.0059L3.1218 respectively. The results additionally showed that length-length relationships (LLRs) were significantly correlated (r²>0.985, P<0.001). This study aims to contribute to the Bayesian hierarchical approach used in LWR calculations in the FishBase database. Additionally, 11 LWRs were gathered from 11 studies carried out between 1984 and 2021 in different marine waters. The present study is an evaluation of previous scientific studies from different areas. The value of the b slope for E. golanii varies between 2.626 and 3.443. The mean value of b was 3.0750 and the median value of b was 3.0435, and the Log10 a and b plot was used to detect outliers.